A formação continuada de professores do campo e a Refocar: rearticulação entre o movimento nacional da educação do campo e a modalidade educacional – região Sudoeste do Paraná – 2015-2020 - Borges, Luciane Cerati (2021)
The following Master’s Thesis locates itself in the Post-Graduation Program in Education – Master’s Degree, Campus Francisco Beltrão/PR, of the State College of Western Paraná (Unioeste), area of concentration in Education, Research Line: Culture, Educational Processes and Formation of Teachers. The research’s theme has as its central category the continued formation of teachers from Public Schools located in the rural area, lined up with the perspective of the National Movement for Field Education, guaranteed by the Federal Decree n. 7.352/2010 and the Resolution n. 4.783/2010 GS/SEED, which created the modality of Basic Field Education. This research takes as research problem, the processes and the productions of extension projects from the Network of Formation and Strengthening of Public Field Schools: Paths of Knowledge and Resistance (Refocar), in a context of rearticulation of public schools located in the rural area with the perspective of the National Movement for Field Education, based on the modality of Basic Field Education, in reference of the continued formation of teachers. Objectifying itself in analyzing the process and potentialities of the continued formation of teachers in the scope of Refocar, through the Rearticulation of Field Public Schools into the National Movement for Field Education based in the modality of Basic Field Education. For that being based in the historical process of EdoC with Munarim (2008;2012), Molina (2012), Caldart (2002, 2008, 2012), Leite (1999), Ribeiro (2013), Silva (2013), Ghedini (2017), Souza (2013;2017;2018), aiming to comprehend the continued formation of teachers of public field schools, with Algebaile (2004), Arroyo (2007), Martins (2008.2020), Santos (2014), among others. Seeks it also the basis of legal documents (BRASIL, 2002; 2006; 2008; 2010a, 2010b) and Paraná (2006; 2010; 2011). This research gets justified because, analyzing the continued formation of teachers in the current social conjuncture, in the specificity of Field Education, requires a comprehension on the totality of this social production. That’s because this modality is imbricated with the People’s Rural Social Movements (MSPdoC), once that “the field education is a phenomena of the current Brazilian reality, starring the workers of the field and its organizations” (CALDART, 2012, p. 257). The research guides itself by the qualitative approach, the adopted methodology will be case study, alongside semi structured interviews with document analysis and complementing itself with procedures from the bibliographical research. Three chapters compose the research: the first presenting the theoric-methodological assumptions of the research analysis and the implied categories referred to the fight for land and the MSPdoC, in the projects of education and continued formation of teachers. The second registers the practices of continued formation of teachers realized in Public Field Schools from Southwestern Paraná, comprehending its assumptions in the perspective of the Movement for Field Education. The third characterizes the continued formation of teachers in the context of REFOCAR and analyzes the potentialities produced in the scope of the rearticulation of these public field schools. The results achieved and here presented account that the continued formation of teachers, in the scope of REFOCAR, showed a formative potentiality in the “Doings” of the public field school, once that, from the experience of articulating the permanent study of educators with the accompaniment of the pedagogical work of schools, produced feelings of collective belonging and identity, allowing for the self-recognition as educator of the Public Field School, taking the modality of Basic Field Education as a tool and legal support, in the perspective of the National Movement for Field Education.